EVALUASI KEBUTUHAN PEGAWAI UNTUK MENINGKATKAN KINERJA PADA KANTOR DINAS PERUMAHAN, KAWASAN PERMUKIMAN, DAN PERTANAHAN KOTA BEKASI - Siti Rahmah; Hasanuddin; Jumawan; Cahyadi Husadha; Tutiek Yoganingsih (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2022)
ABSTRACT This study aims to determine how employee evaluation improves performance. the research method used is the descriptive qualitative method. The theory used in this study is the evaluation criteria of William N Dunn (2003). Research data using primary data and secondary data. Primary data is obtained through interviews with informants who know the problem to be studied, while secondary data is obtained through books, scientific journals, and government documents/regulations. The results of this study indicate that there is a delay in completing work and an excess workload given by employees so that some employees have to complete work outside of working hours and the rules of job analysis and workload analysis at the Government Office of the Housing, Settlement, and Land of Bekasi City are still not suitable following which has been specified.